To be serrate or pinnate: diverse leaf forms of yarrows (Achillea) are linked to differential expression patterns of NAM genes. (18th December 2017) - Sha, Sha; Chen, Duo; Liu, Ming; Li, Ke-Lai; Jiang, Chen-Kun; Wang, Dong-Hui; Guo, Yan-Ping
Abstract: Background and Aims: To understand the link between species diversity and phenotype developmental evolution is an important issue in evolutionary biology. Yarrows in the genus Achillea (Asteraceae) show a great diversity in leaf serrate or pinnate dissection patterns. In Arabidopsis thaliana, the development of leaf serration requires the activity of the transcription factor CUC2. Does this regulator also work for leaf dissections of the Asteraceae plants? If so, how do the conserved regulatory 'tools' work differently to produce diverse leaf forms? Methods: Seedling leaf morphology was observed, and morphogenesis of leaf serration or lobes was examined by scanning electron microscopy (SEM). NAM genes, orthologues of arabidopsis CUC2, were isolated from A. acuminata with serrate leaves and A. asiatica with three-pinnatisect leaves, respectively. By means of whole-mount in situ mRNA hybridization and two quantitative gene expression assays, the droplet digital PCR (ddPCR) and quantitative real-time PCR (qPCR), expression patterns of the NAM genes during leaf dissection development were checked in both species for comparison. Key Results: For both species, the development of leaf dissection initiated when a leaf blade was about 300–400 µm long. In A. acuminata, in situ hybridization showed NAM expression signals at leaf margins where teeth are growing, or later on, in the sinuses of the teeth, whilst in A. asiatica, hybridization signals appear not only on leaf margins but further on the margins of leaf lobes. Both ddPCR and qPCR revealed a continuous decline of AacNAM expression from the early to the late developmental stages of a single leaf of A. acuminata, whereas a relatively long maintenance and fluctuation of AasNAM expression was seen in a leaf of A. asiatica . Conclusions: Differential spatiotemporal patterns of NAM expression were found between the two yarrow species during development of leaf dissection. This study provides the first evidence for NAM activity in the development of leaf dissection of the Asteraceae plants, and demonstrates that leaf form diversity is correlated to the altered NAM expression dynamic.